Early activation of rat skeletal muscle IL-6/STAT1/STAT3 dependent gene expression in resistance exercise linked to hypertrophy. - Gwénaëlle Begue (Public Library of Science (PLoS), 2013)
Cytokine interleukin-6 (IL-6) is an essential regulator of satellite cell-mediated hypertrophic muscle growth through the transcription factor signal transducer and activator of transcription 3 (STAT3). The importance of this pathway linked to the modulation of myogenic regulatory factors expression in rat skeletal muscle undergoing hypertrophy following resistance exercise, has not been investigated. In this study, the phosphorylation and nuclear localization of STAT3, together with IL-6/STAT3-responsive gene expression, were measured after both a single bout of resistance exercise and 10 weeks of training. Flexor Digitorum Profundus muscle samples from Wistar rats were obtained 2 and 6 hours after a single bout of resistance exercise and 72 h after the last bout of either 2, 4, or 10 weeks of resistance training. We observed an increase in IL-6 and SOCS3 mRNAs concomitant with phosphorylation of STAT1 and STAT3 after 2 and 6 hours of a single bout of exercise (p<0.05). STAT3-dependent early responsive genes such as CyclinD1 and cMyc were also upregulated whereas MyoD and Myf5 mRNAs were downregulated (p<0.05). BrdU-positive satellite cells increased at 2 and 6 hours after exercise (p<0.05). Muscle fiber hypertrophy reached up to 100% after 10 weeks of training and the mRNA expression of Myf5, c-Myc and Cyclin-D1 decreased, whereas IL-6 mRNA remained upregulated. We conclude that the IL-6/STAT1/STAT3 signaling pathway and its responsive genes after a single bout of resistance exercise are an important event regulating the SC pool and behavior involved in muscle hypertrophy after ten weeks of training in rat skeletal muscle.